The significance and role of godparents in wedding songs from Kosovo and Metohija - Miljković Marija D. (Zbornik Radova Filozofskog Fakulteta u Prištini)
Among the numerous motifs celebrated in the lyrical folk poems of the Serbs from Kosovo and Metohija, there is also the motif of spiritual kinship (godfatherhood). Using examples from folk lyrical poems from this region, we examined the prevalence of the godfatherhood motif and the function of godfathers primarily in wedding poems where this motif is most prevalent. Poems collected by Ivan Stepanovich Yastrebov, Dena Debeljković, Vladimir Bovan, as well as poems published in the Constantinople Herald, were analysed. We noticed the significant importance of this type of spiritual kinship. Like in the folk tradition, poems also show that the godfather is considered almost equal to a saint in importance, and that his role in an individual's life cycle is significant, as is especially highlighted in the wedding rituals described and preserved in wedding oral-poetic material. In the complex ritual of transition, the godfather mediates between the groom and the ancestors, and the act of gifting, which is essential in the ritual itself and described in the poems, is associated with the sacrifice offered to the ancestors. We would emphasize those poems where, in terms of importance, the motif of spiritual kinship is equated with the motif of love. The preservation of the inviolability of this spiritual bond in some poems depends solely on the individual. Regardless of whether the godfather is seen as a mediator between the living and the ancestors, as an indispensable helper to the groom/initiate, as a potential betrayer, or as a potential opponent/enemy, the poems point to the sacredness that this spiritual bond inherently represents.